Optimization of Extraction and Measurement Methods in the Determination of Total Iron (Fe) Content in Anti-Anemia Multivitamin Capsule Samples - Ismail, Rohmat; Erlangga, Manasye; Wahyuningtyas, Irma; Prihatini, Esti (Jurnal Beta Kimia, 2025)
Iron (Fe) is a transition metal that plays a critical role in human life, particularly as a micronutrient. The objective of this study is to optimize and ascertain the most appropriate method for measuring the total Fe content of anti-anemia multivitamin capsule samples, thereby ensuring the accuracy of the measurement results. The determination of total Fe content can be achieved through two metal extraction methods, namely wet digest and dry ashing methods, and two metal measurement methods, namely UV-Vis spectrophotometer and atomic absorption spectrophotometer (AAS). The findings revealed that the measurement of total Fe content by UV-Vis spectrophotometer through the dry ashing extraction method yielded a lower value (20.92 ± 0.29 mg/g) compared to the wet digest method (67.91 ± 0.83 mg/g). Furthermore, the Fe content determined by AAS analysis exhibited a reduced value in the dry ashing extraction method (1.42 ± 0.02 mg/g), while the wet digest extraction method yielded a substantially higher value (72.91 ± 4.12 mg/g). Statistical tests with the Duncan method revealed that the wet digest extraction method with UV-Vis spectrophotometer measurements is the most effective method for determining the total Fe content, with a significance level equivalent to the theoretical reference value (67.85 ± 0.03 mg/g).